Reckoning of Ground Water Quality in Slum Areas of Tenali Town by Nemerow’s Pollution Index - M. V. Raju, Md. B. Wasim Akram, T. L. Rishi Vardhan, U. Hemanth, M. Satish Kumar (International Journal of Advanced Science and Technology, 2020)
Slum, the area where highly populated, which consists of closely packed has squatter settlements, poor in quality of water supply and lack of proper toilet facilities and other sanitary requirements. According to UN- Habitat, about thirty three percentage of urban developing population were living in slums. In India, Bombay, where highest number of people is living in slums, nearly half of the populations in Bombay were living in small shacks, which are surrounded by open drains. The study aims in evaluating groundwater quality status in the slums of Tenali Municipal Corporation consist of 59 slums by the Nemerow’s Pollution Index method (NPI) and its portability during winter season.